EFEKTIVITAS LATIHAN FISIK TERSTRUKTUR TERHADAP PENURUNAN INDEKS INSOMNIA PADA PEROKOK - Kumboyono Kumboyono; Shila Wisnasari; Titin Andri Wihastuti (Jurnal Keperawatan Malang, 2025)
Background: Smokers frequently experience insomnia, a sleep disturbance linked to nicotine’s stimulating properties that negatively impact sleep quality. Non-pharmacological approaches, such as structured physical exercise, have gained attention as alternative interventions for insomnia management. Purpose: The study aimed to evaluate the effectiveness of structured physical exercise in reducing insomnia severity among young adult smokers. Methods: This study employed a quasi-experimental design with a pretest-posttest model and control group. A total of 40 young adult smokers were recruited as participants and proportionally assigned to either the intervention or control group, with 20 individuals in each. The intervention group underwent a structured physical exercise program for four weeks, performed three times per week for 30 minutes per session, while the control group received health education materials. Insomnia severity was measured using ISI (the Insomnia Severity Index). Data were analyzed using the Wilcoxon signed-rank test for within-group comparisons and the Mann–Whitney U test for between-group differences. Result: The findings revealed a significant reduction in ISI scores within the intervention group, with an average difference of 4.40 (p<0.001), whereas the control group showed a smaller, non-significant reduction of 0.80 (p=0.086). Structured physical exercise proved to be statistically more effective in decreasing insomnia severity compared to health education (p=0.001). Implication: Community nurses can adopt promotive strategies by implementing structured physical exercise interventions to effectively reduce insomnia severity among young adult smokers. This non-pharmacological approach can be systematically integrated into public health programs to support improved sleep quality and overall health outcomes. Keywords: Insomnia; Non-pharmacological intervention; Physical exercise; Smokers; Sleep